The ‘foremost ornithological mystery of Costa Rica’: Amazilia alfaroana Underwood, 1896 - Kirwan, Guy M.; Collar, Nigel J. (Zootaxa, 2016)
The hummingbird Amazilia alfaroana is known from a single specimen, collected on the Volcán de Miravalles, in north-west Costa Rica, in September 1895. Since the early 20th century, the taxon has been almost always been treated as a subspecies of Indigo-capped Hummingbird A. cyanifrons, which is otherwise endemic to Colombia, although it has also been tentatively suggested that the holotype might represent a hybrid between two unnamed species of trochilids. Our detailed analysis of the specimen reveals species-level differences between A. alfaroana and A. cyanifrons, and no evidence of characters that might suggest a hybrid between two species known to occur in the relevant region. Until molecular techniques have been brought to bear, we believe that A. alfaroana is best treated as a possibly now extinct species.